The Healthy Crew, Clean Vessel, and Set Departure Date Triad: Successful Control of Outbreaks of COVID-19 On Board Four Cargo Vessels. Issue 5 (9th October 2021) - Codreanu, Tudor A.; Pingault, Nevada; O'Loughlin, Edmond; Armstrong, Paul K.; Scalley, Benjamin
Abstract: Background: A variety of infectious diseases can cause outbreaks on board vessels, with both health and economic effects. Internationally, Coronavirus Disease 2019 (COVID-19) outbreaks have occurred on numerous cruise and cargo vessels and the containment measures, travel restrictions, and border closures continue to make it increasingly difficult for ship operators world-wide to be granted pratique, effect crew changes, and conduct trade. An effective outbreak management strategy is essential to achieve the outcome triad – healthy crew, clean vessel, and set departure date – while maintaining the safety of the on-shore workers and broader community and minimizing disruption to trade. This report describes the principles of COVID-19 outbreak responses on four cargo vessels, including the successful use of one vessel as a quarantine facility. Methods: Established principles of management and the experiences of COVID-19 outbreaks on cruise ships elsewhere informed a health-lead, multi-agency, strict 14-day quarantine (Q) regime based on: population density reduction on board; crew segregation; vessel cleaning and sanitation; infection risk zones, access, and control measures; health monitoring; case identification and management; food preparation and delivery; waste management control; communication; and welfare and security. Findings: Sixty-five crew were diagnosed with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection (range 2-25; attack rate 10%-81%; 15 asymptomatic). No deaths were recorded, and only one crew was hospitalized for COVID-19-related symptoms but did not require intensive care support. Catering crew were among the cases on three vessels. All non-essential crew (n-EC) and most of the cases were disembarked. During the vessel's Q period, no further cases were diagnosed on board, and no crew became symptomatic after completion of Q. The outbreak response duration was 15-17 days from initial decision. No serious health issues were reported, no response staff became infected, and only two Q protocol breaches occurred among crew. Interpretation: Despite increasing risk of outbreaks on cargo vessels, maritime trade and crew exchanges must continue. The potential consequences of COVID-19 outbreaks to human life and to trade necessitate a balanced response. The principles described can offer health, financial, operational, and safety advantages.